Molecular diagnosis of bcr-abl fusion gene in CML patients using Monoplex-Two Steps- Reveres Transcriptase–Polymerase Chain - Dhahii, Maysaa A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Chronic myeloid leukemia (CML) is a stem cell disorder associated with an acquired chromosomal abnormality, Philadelphia chromosome (Ph), which arises from the reciprocal translocation of part of long arm of chromosome 9, in which proto-oncogene ablson gene (abl) is located, to long arm of chromosome 22, in which break point cluster region gene (bcr) is located. The bcr-abl fusion gene can be detected using several molecular methods. For its simplicity, rapidity, and sensitivity, Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) is one of the most common techniques used for analyzing whether a target gene is being expressed or not. Patients and methods: Venous blood (VB) sample from hematologically and clinically diagnosed 34 CML patients and10 acute lymphoid leukemia (ALL) were collected. Also, 10 healthy individuals were included as health negative control. RNA was extracted from these samples using commercial kit. Molecular screening for the presence of bcr-abl in these samples was done using Monoplex- Two Steps-Reverse Transcriptase-Polymerase Chain Reaction (M-TS-RT-PCR). Amplified products were electrophoresid in 1.5% agarose gel. Results: The results showed that all CML patients were positive for bcr-abl while all the others were negative for this gene. Conclusion: Monoplex - Two steps – RT-PCR has been successfully used to detect and subtype bcrabl fusion gene. It is a fast and effective technique that should be done upfront at diagnosis in patients with CML, as its molecular type is crucial in the treatment follow-ups.